Quantitative Whole Genome Sequencing of Circulating Tumor Cells Enables Personalized Combination Therapy of Metastatic Cancer - Gulbahce, Natali; Magbanua, Mark Jesus M; Chin, Robert; Agarwal, Misha R; Luo, Xuhao; Liu, Jia; Hayden, Daniel M; Mao, Qing; Ciotlos, Serban; Li, Zhenyu; Chen, Yanxiang; Chen, Xingpeng; et al. (Cancer research (Chicago, Ill.), 2017)
Much effort has been dedicated to developing circulating tumor cells (CTC) as a noninvasive cancer biopsy, but with limited success as yet. In this study, we combine a method for isolation of highly pure CTCs using immunomagnetic enrichment/fluorescence-activated cell sorting with advanced whole genome sequencing (WGS), based on long fragment read technology, to illustrate the utility of an accurate, comprehensive, phased, and quantitative genomic analysis platform for CTCs. Whole genomes of 34 CTCs from a patient with metastatic breast cancer were analyzed as 3,072 barcoded subgenomic compartments of long DNA. WGS resulted in a read coverage of 23× per cell and an ensemble call rate of >95%. These barcoded reads enabled accurate detection of somatic mutations present in as few as 12% of CTCs. We found in CTCs a total of 2,766 somatic single-nucleotide variants and 543 indels and multi-base substitutions, 23 of which altered amino acid sequences. Another 16,961 somatic single nucleotide variant and 8,408 indels and multi-base substitutions, 77 of which were nonsynonymous, were detected with varying degrees of prevalence across the 34 CTCs. On the basis of our whole genome data of mutations found in all CTCs, we identified driver mutations and the tissue of origin of these cells, suggesting personalized combination therapies beyond the scope of most gene panels. Taken together, our results show how advanced WGS of CTCs can lead to high-resolution analyses of cancers that can reliably guide personalized therapy. .